IMPLEMENTASI APLIKASI WEBSITE SEKOLAH TAMAN KANAK-KANAK DEWI SARTIKA BANDUNG - Lukman, Achmad; Fahlena, Hilda; Anuwiksa, I Wayan Palton (Jurnal AbdiMas Nusa Mandiri, 2025)
Community service activities held at Dewi Sartika Bandung Kindergarten School are based on several areas for improvement in publicizing the school's activities to the community. The school only had social media such as Instagram and Facebook during its establishment. Another shortcoming is the documentation of new student registration, which still uses registration forms, hard copies of family cards, and identity cards of prospective students' parents. The effectiveness of document storage could be improved. It is still prone to data loss, so it is necessary to have digital data storage to overcome these shortcomings by creating a website that is integrated with digital prospective student data collection. The method applied to measure success in this community service activity is quantitative method, namely giving a questionnaire which is then calculating to obtain a percentage value of success from this activity.  The results of community service activities carried out at the school are in the form of a website that can be accessed by teachers, parents of students, prospective school students, and public society and is expected to help with administrative work at the Dewi Sartika Bandung Kindergarten. The percentage of success of the website that has been created is in the “sufficient/normal” category, which is represented by a percentage value of 46.5 %.